STARTEGI PENGEMBANGAN POTENSI DESA WISATA BEJIHARJO DALAM RANGKA MENINGKATKAN LAMA KUNJUNG DI KABUPATEN GUNUNGKIDUL - , WAHYU DITAHUTAMA, Fahmi Prihantoro,S.S ,S.H, M.H ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Today the society has had a tourist awareness especially in Yogyakarta Special Region. This is evidenced by the development of the tourism sector in various areas in Yogyakarta where today many are born various tourist village offers its own uniqueness. In Gunungkidul, there are currently one of the tourism village that is rapidly being developed namely Bejiharjo Tourism Village. This tourism village has a natural beauty that is captivating and offers many interesting tourism attractions as alternative tourism options in Gunungkidul. Behind natural beauty Bejiharjo Tourism Village also have people who care and are aware that travel can be developed in the region. The awareness resulted in the rapid growth of the Bejiharjo Tourism Village. Research conducted at the Tourism Village Bejiharjo conducted to determine the potential of what is contained in these tourist villages, tourist activities to do, the promotion and development as well as analyzing the potential that is still widely available in the Bejiharjo Tourism Village and development that can be done so that the number of tourists that has a lot of the old can be compensated by an increase in visits. By knowing everything about the village tourism are expected to be a learning experience for the community in developing the Tourism Village Bejiharjo there is still potential in village tourism and preserving the environment in which tourism activities are done.